The first approach to dynamic modeling of a solar vanadium redox flow cell - Nuno Delgado (2021)
The increasing offer of energy, especially electricity from renewable sources, has been fueling the investment in energy storage technologies. However, most of the energy harvesting technologies produce non-dispatchable electricity. The solar redox flow cell (SRFC) technology stands out by converting sunlight into storable energy. The latter is easily converted into electricity. However, there are challenges that need to be addressed before SRFCs become commercially available. Phenomenological models are a powerful tool that can be used to accelerate the development of any technology. This work reports the first multidimensional, dynamic and phenomenological model of a vanadium SRFC. The mass and momentum conservation equations are incorporated in the model to simulate the electrolyte flow. The charge transport is simulated by implementing the charge conservation, the Nernst-Planck and drift-diffusion equations. The photoelectrochemical and electrochemical reactions are simulated using the Butler-Volmer equation. The model is validated against experimental data of a vanadium SRFC using a cadmium sulfide semiconductor (n-type). The energy band shifting for different bias potentials and the accumulation and depletion of charges at the space charge region are simulated. The photopotential is determined using the minor carrier concentration and it is demonstrated to be equivalent to the potential difference between the quasi-Fermi energy levels of the electrons and holes. The impact of recombination mechanisms in the performance of the SRFC is analyzed; the surface recombination competes with surface reactions, affecting the onset potential, while non-surface recombination mechanisms affect the concentration of holes, decreasing the maximum current density.